Curcumin Quantum Dots Mediated Degradation of Bacterial Biofilms - Singh, Ashish K.; Prakash, Pradyot; Singh, Ranjana; Nandy, Nabarun; Firdaus, Zeba; Bansal, Monika; Singh, Ranjan K.; Srivastava, Anchal; Roy, Jagat K.; Mishra, Brahmeshwar; Singh, Rakesh K. (Frontiers in Microbiology, 2017)
Bacterial biofilm has been reported to be associated with more than 80 percent of bacterial infections. Curcumin, a hydrophobic polyphenol compound, has anti-quorum sensing activity apart from having anti-microbial action. However, its use is limited by its poor aqueous solubility and rapid degradation. In this study, we attempted to prepare quantum dots of the drug curcumin in order to achieve enhanced solubility and stability and investigated for its antimicrobial and antibiofilm activity. We utilized a newer two-step bottom up wet milling approach to prepare Curcumin Quantum Dots (CurQDs) using acetone as a primary solvent. Minimum inhibitory concentration against select gram-positive and gram-negative bacteria was performed. The antibiofilm assay was performed at first using 96-well tissue culture plate and subsequently validated by Confocal Laser Scanning Microscopy. Further, biofilm matrix protein was isolated using formaldehyde sludge and TCA/Acetone precipitation method. Protein extracted was incubated with varying concentration of Curcumin quantum dots for 4 hrs and was subjected to SDS-PAGE. Molecular docking study was performed to observe interaction between curcumin and phenol soluble modulins as well as curli proteins. The biophysical evidences obtained from TEM, SEM, UV-VIS, fluorescence, Raman spectroscopy and zeta potential analysis confirmed the formation of curcumin quantum dots with increased stability and solubility. The MICs of curcumin quantum dots, as observed against both select gram positive and negative bacterial isolates, was observed to be significantly lower than native curcumin particles. On TCP assay, Curcumin observed to be having antibiofilm as well as biofilm degrading activity. Results of SDS-PAGE and molecular docking have shown interaction between biofilm matrix proteins and curcumin. The results indicate that aqueous solubility and stability of Curcumin can be achieved by preparing its quantum dots. The study also demonstrates that by sizing down the particle size has not only enhanced its antimicrobial properties but it has also shown its antibiofilm activities. Further, study is needed to elucidate the exact nature of interaction between curcumin and biofilm matrix proteins.